Yes, women play mamulengo: narratives of women players (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article presents two (auto)biographical narratives of female actors from the Federal District of the Popular Puppet Theater, specifically the Mamulengo. Anchored in decolonial perspectives and feminism, in the context of the periphery of the West, the article proposes to report on how women puppeteers occupy the center of the wheel, playing the leading roles.
Keywords: women; culture; (auto)biographical research; decoloniality; education